Cone beam computed tomographic assessment of radiographic changes after indirect pulp capping using diode lasers and silver diamine fluoride in permanent molars with deep carious lesions - EL-TAYEB, Mohamed M.N.; NABEEL, Mohamed (International Arab Journal of Dentistry (IAJD), 2023)
Aim: To compare the preservation of pulp vitality by indirect pulp capping using Diode laser and Silver Diamine Flouride in management of deep carious lesions. Methods: Thirty patients with an age range of 18-46 years were selected and randomly divided into 3 equal groups: Group 1 (Control group): indirect pulp capping was performed using Biodentine, Group 2: Diode laser with an output power of 0.5 watt was applied before Biodentine placement, and Group 3: Application of Silver Diamine Flouride followed by Biodentine. Pre-operative clinical assessment and radiographs were performed before intervention and then the patients received their treatment and final restorations. Follow-up with clinical assessments was performed after 3 and 6 months. Cone beam computed tomography was performed at the day of intervention and after 6 months. Clinical and Radiographic data were collected, tabulated and statistically analyzed to compare between the success rates of indirect pulp capping using diode laser, Silver Diamine Flouride and Biodentine in management of deep carious lesions. Results: The results of clinical assessment for all groups have shown success rate of 100%. The remaining dentin thickness was significantly increased in all study groups after application of intervention. Also, the remaining dentin density showed significant increase in all groups, where Diode laser application with an output power of 0.5 watt group was significantly higher than the control group, with no significant difference between other groups. Conclusions: Within the limitations of the current study, the following can be concluded: 1. Using Biodentine in indirect pulp capping is the treatment of choice in management of deep carious lesions. 2. Silver Diamine Flouride can be used as an alternative indirect pulp capping material. 3. Diode laser can show promising results in terms of Cavity Disinfection & can have better biomodulating outcomes on the pulpal tissue healing and repair.